Late medieval heresy : new perspectives : studies in honor of Robert E. Lerner - Bailey, Michael David, 1971-; Field, Sean L. (Sean Linscott), 1970-; Lerner, Robert E. (Heresy and inquisition in the Middle Ages, 2018)
From the Gregorian reforms to the Protestant Reformation, heresies and heretics helped shape the religious, political, and institutional structures of medieval Europe. Within this larger history of religious ferment, the late medieval period presents a particularly dynamic array of heterodox movements, dissident modes of thought, and ecclesiastical responses. Yet recent debates about the nature of heresy in the twelfth and thirteenth centuries have too easily created an impression of the period after 1300 as merely an epilogue to the high medieval story.0This volume takes the history of heresy in late medieval Europe (1300-1500) on its own terms. From Paris to Prague and from northern Germany to Italy and even extending as far as Ethiopia, the essays shed new light on a vibrant world of audacious beguines, ardent Joachites, Spiritual Franciscans, innovative mystics, lay prophets, idiosyncratic alchemists, daring magicians, and even rebellious princes locked in battles with the papacy. As befits a collection honoring the pioneering career of Robert E. Lerner, the studies collected here combine close readings of manuscripts and other sources with a grounding in their political, religious and intellectual contexts, to offer fresh insights into heresies and heretics in late medieval Europe.